Observer-based sliding-mode fault-tolerant consistent control for hybrid event-triggered multi-agent systems - Xia, Dexian; Fu, Xingjian (Zielona Góra: Uniwersytet Zielonogórski)
An observer-based hybrid event-triggered sliding mode fault-tolerant consistent control strategy is proposed for actuator faults in nonlinear second-order leader-follower multi-agent systems. A fault observer is designed to obtain the velocity and additive fault of the agents at the current moment. In order to save network resources and avoid the proliferation of actuator fault information, a hybrid event-triggered mechanism is given based on the actuator fault output from the fault observer. Then, a sliding mode fault-tolerant control strategy is investigated based on the speed and hybrid event-triggered mechanism of the fault observer output and combined with a linear sliding mode surface.
Keywords: multi-agent systems; fault-tolerant control; fault observers; sliding mode control; hybrid event-triggered mechanisms